GARDNER, F. and COOMBS, S.J. -eds.- (2010) Researching, Reflecting and Writing about Work: guidance on training course assignments and research for psychotherapists and counsellors. London, Routledge. 150 pages. - Sorensen, Nick (Revista Fuentes, 2012)
GARDNER, F. and COOMBS, S.J. -eds.- (2010) Researching, Reflecting and Writing about Work: guidance on training course assignments and research for psychotherapists and counsellors. London, Routledge. 150 pages.